2015
DOI: 10.21831/jim.v12i1.11741
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Kecukupan Modal (CAR), Pengelolaan Kredit (NPL), dan Likuiditas Bank (LDR) Terhadap Probabilitas Kebangkrutan Bank (Studi pada Bank Umum Swasta Devisa yang tercatat di BEI tahun 2009 – 2013)

Abstract: The purpose of this research is to provide empirical evidence about using bank financial ratio to predict bank bankruptcy. The variables which used are seven financial ratios, CAR (capital adequacy ratio), NPL (non performing loan), and LDR (loan to deposit ratio). The statistic methods which is used to test on the research hypothesis is logit regression.The sample of this research was extracted using purposive sampling method, comprising 7 banks taken from BEI for the period of 2009, 2010, 2011, 2012, 2013. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1
11

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 0 publications
1
6
1
11
Order By: Relevance
“…It indicated that the bank had complied with the provision of Bank Indonesia so it could be said that conventional commercial banks already had very strong capital. This study supported researches conducted by Sumantri & Jurnali (2010), Nugroho (2012), Hidayati (2015), and Prasidha & Wahyudi (2015)…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…It indicated that the bank had complied with the provision of Bank Indonesia so it could be said that conventional commercial banks already had very strong capital. This study supported researches conducted by Sumantri & Jurnali (2010), Nugroho (2012), Hidayati (2015), and Prasidha & Wahyudi (2015)…”
Section: Discussionsupporting
confidence: 89%
“…This study supported Prasidha & Wahyudi's (2015) study which found that LDR could not be used to predict the occurrence of troubled conditions of banks. This research was not in line with the researches done by Prajitno (2009), Sumantri & Jurnali (2010), Nugroho (2012) and Hidayati (2015).…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…the NPL ratio can be used to predict Financial Distress [4], and CAR can be used to predict Financial Distress [5]. Although there are studies that CAR, GCG, LDR, and NPL did not affect the condition of the Financial Distress [6], NPL and LDR affected Financial Distress [7], whereas the CAR, NPL and LDR ratio did not affect Financial Distress [8]. One of the studies regarding the application of the Bankometer Model in Islamic Banking and Conventional Banking companies, the results of which showed that the Bankometer Model could be used to predict Financial Distress [9].…”
Section: Introductionmentioning
confidence: 99%